Synthesis and electrochemistry of complexes containing the ferrocenyl-phosphine ligand PPh(CH2CH2- [eta] 5-C5H4)2Fe - Adams, Julian J.; Curnow, Owen J.; Huttner, Gottfried; Smail, Samuel J.; Turnbull, Mark M. (Journal of organometallic chemistry, 1999)
Treatment of the tethered bis(cyclopentadienyl)-phosphine compound bis(2-cyclopentadienylethyl)phenylphosphine (1) produces moderate yields (40-50%) o…